Volatile Benzene Derivatives as Honey Biomarkers - Jerković, Igor (Synlett, 2013)
The biodiversity of low-molecular-weight volatile benzene derivatives has been a driving force for the discovery of specific or nonspecific biomarkers that can be used to determine the botanical origin of honey. Stimulated by the challenge of their structure identification and by the possibility of developing fingerprinting methods, exploratory studies are summarized in this paper with a short overview of their possible formation pathways.
Keywords: natural products; bioorganic chemistry; aldehydes; carboxylic acids; esters